Carbon Emissions Disclosure in Moderating Managerial Ownership and Political Connections towards Tax Aggressiveness - Vrencia Liviana Benny; Elfina Astrella Sambuaga; Kenny Fernando; Budi Kurniawan (Universitas Negeri Semarang, 2025)
Purposes: This study aims to provide empirical evidence on Carbon Emissions Disclosure (CED) in mediating the relationship between Managerial Ownership and Political Connections, namely Managerial Characteristics, towards Tax Aggressiveness in Indonesia.Methods: The analysis was conducted on companies listed on the Indonesia Stock Exchange during 2019-2022, excluding the financial, technology, and property sectors.Findings: The results show that Managerial Ownership significantly influenced Tax Aggressiveness as the managers with ownership tend to be more aggressive in reducing taxes to increase profits. However, Political Connections do not affect substantially Tax Aggressiveness behavior. CED negatively impacted tax payments but did not moderate the relationship between Managerial Ownership or Political Connections toward Tax Aggressiveness.Novelty: The study uniquely observes how companies and managers respond to these nascent regulations, even before full implementation, and highlights the emerging role of carbon emissions disclosure as a new factor influencing corporate tax strategies, providing specific insights from the Indonesian setting. This research presents significant novelty by investigating the relationship between managerial characteristics (managerial ownership and political connections) and tax aggressiveness, specifically moderated by carbon emissions disclosure, within the unique context of Indonesia's newly implemented and evolving carbon regulations. The study uniquely observes how companies and managers respond to these nascent regulations, even before full implementation, and highlights the emerging role of carbon emissions disclosure as a new factor influencing corporate tax strategies, providing specific insights from the Indonesian setting